EXPERIMENTAL EVIDENCE OF THE EXISTENCE ANAMMOX-IN AERATION TANKS CLEANING FACILITIES UKRAINE - and; and (Municipal economy of cities. Series: «Economy science», 2013)
Experiments with immobilized on fibrous media such as activated sludge microorganisms Via The presence of Anammox-process (anaerobic ammonium oxidation) in the aeration number of treatment facilities in Ukraine. Chromatographic analysis of biogas released in Anammox-process showed very high (92-95%) nitrogen. The possibility of using this process to intensify the wastewater from nitrogen-containing compounds.